Biomimetic LBL structured nanofibrous matrices assembled by chitosan/collagen for promoting wound healing. (June 2015) - Huang, Rong; Li, Wangzhou; Lv, Xiaoxing; Lei, Zhanjun; Bian, Yongqian; Deng, Hongbing; Wang, Hongjun; Li, Jinqing; Li, Xueyong
Abstract: This paper reports the fabrication of biomimetic nanofibrous matrices via co-electrospinning of polycaprolactone (PCL)/cellulose acetate (CA) and layer-by-layer self-assembly (LBL) of positively charged chitosan (CS) and negatively charged Type Ⅰ collagen on the nanofibrous matrix. FE-SEM images indicate that the average fiber diameter increased from 392 to 541 nm when the coating bilayers varied from 5 to 20.5. Besides, the excellent biocompatibility and enhanced attachment and spreading of normal human dermal fibroblasts (NHDFs) of prepared nanofibrous mats are confirmed by MTT and SEM results. Furthermore, the LBL structured (CS/collagen)n nanofibrous mats greatly improve the cell migration in vitro, promote re-epithelialization and vascularization in vivo, and up-regulate the expression of collagen Ⅳ and α-tubulin, as well as the Integrin β1 and phosphorylation of focal adhesion kinase (FAK) at Tyr-397. The levels of expressed protein are significantly enhanced with increasing coating bilayers via immunohistochemistry and western blotting analyses. Collectively, these results suggest that the LBL structured biomimetic nanofibrous matrices may enhance cell migration and further promote the skin regeneration by up-regulating the secretion of ECM protein and triggering Integrin/FAK signaling pathway, which demonstrate the potential use of the nanofibrous mats to rapidly restore the structural and functional properties of wounded skin.